2014 IEEE Intelligent Vehicles Symposium Proceedings 2014
DOI: 10.1109/ivs.2014.6856555
|View full text |Cite
|
Sign up to set email alerts
|

Fusion at detection level for frontal object perception

Abstract: Abstract-Intelligent vehicle perception involves the correct detection and tracking of moving objects. Taking into account all the possible information at early levels of the perception task can improve the final model of the environment. In this paper, we present an evidential fusion framework to represent and combine evidence from multiple lists of sensor detections. Our fusion framework considers the position, shape and appearance information to represent, associate and combine sensor detections. Although o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…It consists of finding the best vehicle tracks estimates (ω * ) according to a shape model (P(ω|z 1:t )), prior model (P(ω)) and likelihood model (P(z 1:t |ω)) (Equation 3). Afterwards, this method uses the pose estimate and the latest sensor measurements to update the grid [12].…”
Section: A Lidar Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…It consists of finding the best vehicle tracks estimates (ω * ) according to a shape model (P(ω|z 1:t )), prior model (P(ω)) and likelihood model (P(z 1:t |ω)) (Equation 3). Afterwards, this method uses the pose estimate and the latest sensor measurements to update the grid [12].…”
Section: A Lidar Processingmentioning
confidence: 99%
“…2) LIDAR-based Detection: As described [1], [12], we focus on identifying the inconsistencies between free and occupied cells within the grid map M while incrementally building such map. If an occupied measurement is detected on a location previously set as free, then it belongs to a moving object.…”
Section: A Lidar Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Correct detection of moving objects is the necessary prerequisite to object tracking system. Research efforts have shown the feasibility of detecting moving objects around the car using various sensors, such as video camera [3, 4], light detection and ranging (LiDAR) [5, 6], and radar [7], or through multi‐sensor fusion [8–11]. Camera is easy to be applied and operated in low cost; however, it is hard to measure the distance of the identified objects and camera‐based object detection approaches have lower efficiency under complex shadow and bad weather.…”
Section: Introductionmentioning
confidence: 99%
“…active, tracked, inactive and lost), are used in the model with Markov decision processes to manage the lifetime of a track (Xiang et al , 2015), but an inactive target remains so forever without considering false missing cases. Besides, rather than just monitoring frontal objects (Chavez-Garcia et al , 2014), we consider the perception of objects in 360 degrees in this paper, which is more difficult to keep their tracks constantly.…”
Section: Introductionmentioning
confidence: 99%